Do micro ao macro: aproximações entre oriente e ocidente em Der Jahreslauf - Chiarelli, Ivan [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This research discusses composer Karlheinz Stockhausen's approach to Japanese musical tradition, as presentified in the work DER JAHRESLAUF(1977), focusing on some of the aspects incorporated to the piece from the Japanese tradition and debating the manner by which they were approached by the German composer. The study presents a synopsis of Stockhausen's productions, both theoretical- and compositionalwise, as well as an overview on gagakumusic. It develops from a metalinguistic basis, to which were added topics on intratextuality and narrative, in order to deal with the process of reading and interpreting aesthetic information. Finally, there follows an analysis of the piece DER JAHRESLAUF, identifying discussed topics and debating their musicological and simbolic implications

Este trabalho discute a aproximação do compositor Karlheinz Stockhausen à tradição musical japonesa, presentificada na obra DER JAHRESLAUF(1977), detendo-se sobre alguns aspectos da tradição nipônica incorporados à peça e discutindo a maneira como foram abordados pelo compositor alemão. O estudo apresenta uma sinopse da produção teórico-composicional de Stockhausen, bem como um breve apanhado acerca da música gagaku, e é elaborado a partir de uma base metalinguística, à qual são acrescentados tópicos de intratextualidade e narrativa, com vistas a tratar do processo de leitura e interpretação de informação estética. Por fim, segue-se uma análise da obra DER JAHRESLAUF, localizando os tópicos apontados e discutindo suas implicações musicológicas e simbólicas
Keywords: Stockhausen, Karlheinz 1928-2007; Teoria musical; Música - Japão; Intertextualidade; Intertextuality